IN VITRO INHIBITION ZONE TEST OF BINAHONG (ANREDERA CORDIFOLIA) TOWARDS STAPHYLOCOCCUS AUREUS, ENTEROCOCCUS FAECALIS, ESCHERICHIA COLI, AND PSEUDOMONAS AERUGINOSA - Amertha, IBPM; Soeliongan, S; Kountul, C (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
ABSTRACT This is a true experimental research with post test-only control group design. The study was conducted to test the inhibitory zone of the Binahong leaf extract (Anredera cordifolia) against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa. Binahong leaf extract is prepared using maceration technique, by soaking it in a sealed jar for 24 hours with 95% methanol. Then subsequently filtered using a funnel with filter paper, and the filtrate is collected inside an erlenmeyer. The filtrate then concentrated using a rotavapor, this concentrated extract dissolved into aquadest with a concentration of 50 ppm, 100 ppm and 1000 ppm. By taking a few colonies with a sterile loop into a stock of Staphylococcus aureus, Enterococcus faecalis, Esherichia coli, Pseudomonas aeruginosa then scratch it into MH blood agar medium, and incubate it for 24 hours with a temperature of 370C. The next day, bacterial suspension was made in test tube, which already contains 0.9% NaCl. The suspension tturbidity is equivalent to 0.5 Mc Farland. Bacterial inhibition zone of binahong leaf extract (Anredera cordifolia) is tested using absorbance disc method or better known as the Kirby-Bauer method. First, pour 10 ml of agar medium (± 400C) into a cup (petridish) and then wait until it’s cold. After the medium becomes solid, the suspension of bacteria Staphylococcus aureus, Enterococcus faecalis, Esherichia coli, and Pseudomonas aeruginosa are slowly smeared with sterile cotton sticks on the surface of the media. Soak the paper discs into binahong leaf extract (Anredera cordifolia) with concentrations of 50, 100, and 1000 ppm, for about 5 minutes, and placed it on the surface of the petridish, together with the positive control (amoxicillin) and negative control (aquadest). Then incubate it at 370C for 24 hours. The effectiveness of binahong leaf extract (Anredera cordifolia) inhibition zone, can be determined by measuring the diameter of clear zone around the paper using a sliding-term. Binahong leaf extract (Anredera cordifolia) zone of inhibition is negative, a very slight different is showed by the amoxicillin inhibition zone, for having a clear zone diameter of 28 mm for Staphylococcus aureus and Esherichia coli, and 21 mm for Enterococcus faecalis. This fact is probably caused by several things concerning the mechanism of action of a substance as an anti bacterial of the binahong leaf extract (Anredera cordifolia).